OS FATORES DE MOTIVAÇÃO NA DEFINIÇÃO DE ESTUDANTES ESTRANGEIROS EM MOBILIDADE ACADÊMICA INTERNACIONAL NO BRASIL - Claudia Cristiane dos Santos Silva (Universidade Federal de Santa Catarina, 2013)
Intending to expand the studies about the academic mobility and its various expressions, this article aims to understand the different motivating factors in the definition process for foreign students for a period of study in anoth er country. Understanding the factors that can influence this choice in the context of spontaneous mobility, regarding the country of destination, going through the analysis of personal and academic aspects, as well as the possible relevance of the destin ation image, rescuing the elements that make up the image of this place. Considering this demand, the study was conducted on an exploratory basis, and its empirical data collected through semi -structured interviews were analyzed from the orientation of th e categories of motivation. The results revealed that there is not a standard component that sets the choice of destination, but an interaction between the different aspects, including the elements that make up the country's image.